Designing a Student Performance Monitoring Dashboard Application Using the MVC Method and the Spring Boot Framework at Media Nusantara Citra University - Adi Fitrianto; Donny (GoAcademica Research & Publishing, 2023)
The student academic performance monitoring dashboard is an application used by lecturers at the Faculty of Business and Education, Media Nusantara Citra University to digitally monitor student performance. The monitoring process currently carried out is still manual, which involves both data searching and manual file searching. Apart from that, this data can only be accessed by the academic department and lecturers must make a request first. On the other hand, the large amount of work and busyness of lecturers means that lecturers do not have much time in the process of collecting data for monitoring, while the monitoring process is very important for lecturers to know the progress and results of the learning process of the lecturers' students. Model, View, Controller (MVC) is an application development architecture that emphasizes 3 important components. These three components each have a focus of attention, responsibility and logic so as to speed up performance. For this reason, to solve the problem of monitoring student academic performance, a dashboard application was built using the MVC method. This monitoring dashboard application was built using the Java programming language with the Spring boot framework and is web-based. Spring boot is a framework for the Java programming language which is equipped with a Tomcat server, Annotation technology, and Maven as a Build Manager. With this application, it is hoped that it will make it easier for lecturers to carry out the monitoring process so that the monitoring process can be carried out anytime and anywhere. The output targeted in this research is a Student Academic Performance Monitoring Dashboard application. This research has a Technology Readiness Level (TKT) at level 2 which is expected to be useful for lecturers at Media Nusantara Citra University. This research also targets additional output, namely publication in a national journal indexed at least SINTA 4 with a target publication in November 2023.